Computation of reactive mixed convection radiative viscoelastic nanofluid thermo-solutal transport from a stretching sheet with Joule heating. (2nd November 2022) - Shamshuddin, MD.; Salawu, S. O.; Bég, O. Anwar; Kadir, Ali; Bég, Tasveer A.
ABSTRACT: As a model for electroconductive nanomaterials processing, the article examines incompressible mixed convection nanofluid flow with convective heat transport from a stretching sheet under the impact of Joule heating and radiative heat flux. The transformed non-linear boundary value problem is solved with a robust Chebyshev collocation technique. Validation is conducted with earlier published results. Nanoparticle concentrations are suppressed with increasing chemical reaction parameter and the effect is strongest for copperwater nanofluid and weakest for TiO2 water nanofluid. Increasing Biot number boosts the temperatures for copper and Al2 O3 but reduces it for TiO2 nanoparticles. Increasing heat generation boosts temperatures strongly for Al2 O3 and TiO2 nanoparticles but weakly for copper nanoparticles. Greater thermophoresis parameter strongly boosts temperatures but suppresses nanoparticle concentrations.